Hepatitis B virus genotypes among the Jarawas: A primitive Negrito tribe of Andaman and Nicobar Islands, India - Murhekar, M. V.; Chakravarty, R.; Murhekar, K. M.; Banerjee, A.; Sehgal, S. C. (Archives of virology, 2006)
The Jarawas, a classical hunter-gatherer tribe of Andaman and Nicobar Islands, India, were living in isolation for several centuries. They came into contact with the civilized world recently. Serological studies carried out among them revealed that hepatitis B virus (HBV) infection is hyper-endemic. The present study was carried out to investigate the possible origin of HBV infection in Jarawas. Genotyping, RFLP analysis, sequencing, and sequence analysis revealed the prevalence of HBV genotype C, similar to genotype C detected in Thailand, Vietnam, and Myanmar. In contrast, genotype D was prevalent among other non-Jarawa tribes of the island. These data suggest that HBV infection was transmitted from Indo-China to the Andaman Islands during migration of the Jarawas many centuries ago.